Expression analysis of microRNAs and mRNAs in ovarian granulosa cells after microcystin-LR exposure. (April 2017) - Li, Xiaoyan; Zhuang, Xin; Xu, Tianchi; Mao, Min; Wang, Cong; Chen, Yabing; Han, Xiaodong; Wu, Jiang
Abstract: Microcystin is a cyclic heptapeptide compounds which could cause female mammals' reproductive toxicity. Ovarian granulosa cells (GCs) are essential for the growth and development of follicles. In this study, after mouse granulosa cells (mGCs) treated with microcystin-LR (MC-LR) for 48 h, microRNAs (miRNAs) and mRNAs microarray technology were adopted to detect the expression of miRNAs and mRNAs. The results showed that 125 miRNAs and 283 mRNAs changed significantly, including 50 miRNAs down-regulated (fold change < −1.2), 75 miRNAs up-regulated (fold change > 1.2), 162 mRNAs down-regulated (fold change < −1.15) and 121 mRNAs up-regulated (fold change > 1.15) in treated group compared with the control group. Functional analysis showed that significant changed miRNAs and mRNAs are mainly involved in proliferation, apoptosis, immunity, metabolism and other biological processes of mGCs. By KEGG pathways analysis, we found that differentially expressed miRNAs and mRNAs mainly participated in apoptosis, formation of cancer, proliferation, production of hormones and other related signal pathways. miRNA-gene network analysis indicated that miR-29b-3p, miR-29a-3p, miR-29c-3p, miR-1906, miR-182-5p, growth factor receptor bound protein 2-associated protein 2 (Gab2), FBJ osteosarcoma oncogene (Fos), insulin-like growth factor 1 (Igf1), mannosidase 1, alpha (Man1a) are key miRNAs and genes. The microarray results were validated by real-time fluorescent quantitative PCR (qRT-PCR). Highlights: We firstly report MC-LR could impact the expression of miRNAs and mRNAs in mGCs. We firstly analyzed aberrant expression of miRNAs and mRNAs by bioinformatics in mGCs after MC-LR exposure. Disorder of miRNAs and mRNAs may affect the hormone production and growth of mGCs.